2018
DOI: 10.1111/pde.13587
|View full text |Cite
|
Sign up to set email alerts
|

Clinical algorithm to manage anemia in epidermolysis bullosa

Abstract: Epidermolysis bullosa is a group of rare genetic disorders with multiple organ system involvement. In one severe form, recessive dystrophic epidermolysis bullosa, chronic anemia is common. This report outlines the multifactorial nature of anemia in recessive dystrophic epidermolysis bullosa and presents a practical clinical algorithm based on expert consensus for the diagnosis and treatment of anemia in recessive dystrophic epidermolysis bullosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…Anaemia is a severe complication of both RDEB and JEB5‐11 and is especially difficult to treat. We have shown that anaemia and iron deficiency are already present in the second year of life, correlate with low weight and worsen with age in RDEB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anaemia is a severe complication of both RDEB and JEB5‐11 and is especially difficult to treat. We have shown that anaemia and iron deficiency are already present in the second year of life, correlate with low weight and worsen with age in RDEB.…”
Section: Discussionmentioning
confidence: 99%
“…In our centre, we recommend oral or intravenous iron administration in cases of iron‐deficiency anaemia, but iron supplementation is unpopular with patients as it increases gastrointestinal symptoms such as constipation and stomach pain 44. The optimal strategy for treating anaemia in EB is still under discussion,11 but should involve ongoing supplementation of iron and cofactors for haemoglobin synthesis, minimizing blood loss from wounds and reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The threshold for initiating treatment and the goals of treatment are subject to variation according to discipline and medical condition [ 22 ]. To guide the providers of patients with RDEB and help standardized the management of anemia, a group of experts in EB from Cincinnati Children’s Hospital developed a clinical algorithm to manage anemia in epidermolysis bullosa [ 14 ]. (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Blood transfusions should be considered for cases where Hb levels are consistently below 80 g/L and/or for symptomatic patients who do not respond to other measures [ 4 ]. Recently, a clinical algorithm for the diagnosis and treatment of anemia in RDEB patients was proposed: (i) start enteral iron if Hb ≤ 100 g/L after performing an enteral iron absorption test, as this may help to determine whether parental iron is indicated instead, (ii) consider IV iron if Hb is between 80 and 100 g/L and, (iii) consider blood transfusion if Hb is < 80 g/L [ 14 ]. However, this is an algorithm suggested by one institution, and every patient’s case should be individually decided.…”
Section: Introductionmentioning
confidence: 99%